Digital Transformation in HR Management: Implementation of SIMPEG to Achieve Good Governance at PT. Concord Karawang - Sari Marliani; Umi Narimawati; M. Yani Syafei (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The purpose of this study is to investigate the effect that the introduction of the Employee Management Information System (SIMPEG) has had on the implementation of excellent governance at PT Concord Karawang. A quantitative method based on multiple linear regression analysis is used in this study to look into the relationship between the dependent variable (good governance) and the independent variables (ease of access, administrative efficiency, data transparency, and effect on work productivity). We administered questionnaires to respondents, who were workers using SIMPEG for personnel administration operations, to collect data. According to the findings of the research, it is evident that every independent variable exerts a substantial impact on good governance, as shown by a p-value smaller than 0.05. Based on the results of the regression analysis, it is clear that the variable that measures administrative efficiency has the most significant effect, as shown by the coefficient ²=0.378. This is followed by the variables representing labor productivity (?=0.341), ease of access (?=0.321), and data transparency (?=0.294). Furthermore, the coefficient of determination value of 0.728 indicates that the four independent variables can explain 72.8% of the variation in good governance. The remaining 27.2% of the variation is due to factors that were not investigated. Based on these data, it can be concluded that the deployment of SIMPEG has made a substantial contribution to the improvement of HR governance at PT Concord Karawang. It is possible for the organization to increase administrative efficiency, boost data transparency, and encourage staff productivity via the optimization of this system, which will eventually have a favorable influence on the implementation of good governance. For this reason, it is strongly recommended that constant improvements be made to the implementation of SIMPEG in order to promote more professional and accountable human resource management methods.